The effectiveness of process genre and product genre approaches to teach writing to introvert and extrovert students (the case of the tenth year students of state senior high school 1 Wirosari-Grobogan in the academic year of 2013/2014) - Sumarno, Wahyu Kyestiati ((JELE) Journal Of English Language and Education, 2015)
This present study aims to investigate the effectiveness of Process Genreand Product Genre Approaches to teach writing to introvert and extrovertstudents. A quasi-experimental study with 2x2 factorial designs was conductedto gain answers. Data were collected by using Myers Briggs Type Indicator,observation notes and a pre-and-posttest. Data were analyzed by using T-test,Two-Way Anova, and Tukey test. The findings revealed that first, ProcessGenre Approach was significantly effective to be used to teach writing to boththe introvert and extrovert students; while, the Product Genre Approach wasonly effective to be used to teach writing to the extrovert students. Second,quantitatively, the Process Genre Approach was not significantly more effectiveto be used to teach writing compared to the Product Genre Approach. Third,the students‟ personalities significantly influenced their writing quality, inwhich the extrovert students‟ writings were better than the introvert students‟writings. Fourth, there was a significant interaction occurred between theteaching approaches and the students‟ personalities on their writing quality.Based on the study results, the researcher suggests English teachers to considerusing Process Genre Approach in their writing classes and identify eachstudent‟s personality in the very beginning of lessons, acknowledging that thestudents‟ personalities significantly influence the students‟ writing quality.Keywords: Process Genre Approach; Student’s Personality; Writing Instruction